Design of automatic turn signal of motorcycle based on Arduino Uno - Ryan Febridion Putra; Oriza Candra (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The purpose of this research is to design a series of automatic turn signal lights on and off using GPS and maps to help motorcyclists be comfortable in driving traffic within and between cities, and help motorcyclists use turn signal lights correctly and precisely when turning them on and off. With this tool, riders can turn on and off the turn signal automatically by simply connecting the tool and application to the internet or bluetooth, making it easier for riders to ride motorbikes. This research uses engineering research methods which include system design, hardware design, software design, hardware and software testing, and test analysis. The programming used is Arduino IDE software. The working principle of this system is that the turn signal lights will automatically be driven by a relay, before the device will be connected to maps through a web-based application as a bridge. This web application connects to Maps to get route data and uses a Bluetooth connection via the HC-05 module to send signals to the Arduino Uno R3. After turning, Maps sends a signal back to turn off the turn signal. The test results show the relationship between speed and active time on the automatic turn signal device, that the higher the speed of the vehicle being traveled, the shorter the active time of the turn signal lights to the turn to be passed, and vice versa. So this research is useful for motorists to turn on and off the turn signal automatically.